Implementation of spiritual guidance and counseling for students at jamilurrahman islamic high school bantul - Suhartono Suhartono; Suyono Umar; Agorovi Kuncoro (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2024)
Education is an effort to improve the quality of humans to become pious people. Thus, the provision of guidance and counseling is not only based on psychological and sociocultural principles, but also must understand that humans are creatures of Allah the Exalted. The purpose of this study was to determine the implementation of spiritual counseling guidance carried out at Madrasah Aliyah Jamilurrahman Bantul, Yogyakarta. This research is a field research, researchers use descriptive qualitative research. The objects of this research are school principals, student affairs and counseling guidance teachers. Data collection techniques in this study are interviews, observation and documentation, as for technical data analysis through data reduction, data presentation and conclusions. The results of this study started from school preventive efforts, violations that occurred in the form of minor violations. Handling problematic students is carried out through dialogue directed at understanding religious values. The impact of spiritual counseling guidance indicates a change in behavior for the better. The supporting factor for spiritual counseling guidance is that teachers are given the opportunity to develop themselves and support school residents. As for the inhibiting factors, there are still school residents who do not understand the function of counseling guidance and there are still parents who lack response to student problems that violate school rules